(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
The article reflects on tradition and contemporaneity in the philosophy of training of the puppeteer in Russian schools. Keywords: Pupperteer. Professional qualification. Tradition. Contemporaneity